Sex Differences in Hypercortisolism and Glucose-Metabolism Disturbances in Patients with Mild Autonomous Cortisol Secretion: Findings From a Single Center in China - Ouyang, Ru; Yin, Yaqi; Wang, Jie; Su, Wanlu; Zang, Li; Chen, Kang; Du, Jin; Lyu, Zhaohui; Dou, Jingtao; Mu, Yiming; Gu, Weijun (Frontiers in Endocrinology, 2022)
Background and objective Mild autonomous cortisol secretion (MACS) presents with a marked female preponderance, but whether the sex difference in its distribution has any relevance to the presentation and outcome of the disease is unknown. The aim of this study was therefore to compare biochemical indices of hypercortisolism and impaired glucose metabolism between male and female patients with MACS. Method We enrolled a total of 98 patients with autonomous/possible autonomous cortisol secretion in our study, and indices of hypercortisolism and glucose metabolism were collected and compared between the male and female patients. Logistic regression models were used to evaluate the association between sex and cortisol-secretory ability, as well as between the latter and glucose metabolism. In addition, we conducted further stratified analyses according to the degree of autonomous cortisol secretion and menopausal status. Results Cortisol levels at 00:00 and 08:00 h after a 1-mg dexamethasone suppression test (DST) and low-dose DST were significantly higher in female than in male MACS patients, and the inhibition rate of 1-mg DST was lower in the women than in the men. This significant difference still remained after adjusting for age, BMI, and the course of the disease. Logistic regression analysis revealed a significant association between autonomous cortisol secretion and fasting C-peptide, as well as with the C-peptide-to-glucose ratio in females relative to male patients. In addition, stratified analyses indicated that this association was observed only among women with autonomous cortisol secretion and who were premenopausal. Conclusion The level of autonomic cortisol secretion in female patients with MACS was higher than in male patients, and the association between autonomous cortisol secretory ability and glucose homeostasis was only noted in patients with autonomous cortisol secretion and in premenopausal women. This phenomenon will, however, require closer follow-up.